Síndrome urêmica em cães com doença renal crônica - Gomes, Samadhi Corrêa [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Uremic syndrome, arising from kidney malfunction, consists of a set of systemic changes caused by the accumulation of toxic substances to the body. Since, with the advance of medicine, the animals lived more reaching advanced age and entering thus on track of senility, chronic renal disease, became a common complaint in the routine of the ambulatory. This high rate of morbidity generates an increased need for clarification of pathophysiology involved in this disease. The components of the uremic syndrome include water and sodium imbalance, anemia, intolerance to carbohydrate, neurological disorders, disorders of the gastrointestinal tract, osteoarthritis, immunological incompetence and metabolic acidosis. The clinical manifestations occur in isolation or in combination. In most cases canines patients are subject to an assessment when the kidney disease has evolved to the final stage with uremic syndrome and installed already, under these conditions, the prognosis is reserved

A síndrome urêmica, decorrente do mau funcionamento renal, consiste em um conjunto de alterações sistêmicas provocadas pelo acúmulo de substâncias tóxicas ao organismo. Visto que, com o avançar da medicina, os animais passaram a viver mais alcançando idades avançadas e entrando, portanto, na faixa da senilidade, a doença renal crônica, tornou-se uma afecção comum na rotina dos atendimentos ambulatoriais. Este alto índice de morbidade gera uma maior necessidade de esclarecimento da fisiopatologia envolvida nessa doença. Os componentes da síndrome urêmica incluem desequilíbrio hídrico e de sódio, anemia, intolerância ao carboidrato, distúrbios neurológicos, distúrbios de trato gastrointestinal, osteodistrofia, incompetência imunológica e acidose metabólica. As manifestações clínicas ocorrem isoladamente ou em conjunto. Na maioria das vezes os pacientes caninos são submetidos à avaliação quando a doença renal evoluiu para o estágio final com a síndrome urêmica já instalada e, nessas condições, o prognóstico é reservado
Keywords: Cão - Doenças; Rins - Doenças